Erythrocyte polyunsaturated fatty acid composition is associated with depression and FADS genotype in Caucasians. (14th September 2018) - Cribb, Lachlan; Murphy, Jenifer; Froud, Amy; Oliver, Georgina; Bousman, Chad A.; Ng, Chee H.; Sarris, Jerome
Abstract : Background: Polyunsaturated fatty acids (PUFAs) play an important role in the pathophysiology of major depressive disorder (MDD), related, in part, to their role in inflammatory systems. The enzymes δ-5 and δ-6 desaturase are the rate-limiting steps in the metabolism of PUFAs and are encoded in the genes fatty acid desaturase (FADS) 1 and 2, respectively. Single nucleotide polymorphisms (SNPs) and haplotypes within the FADS gene cluster have been shown to influence PUFA composition. Aim: The objective of this study was to determine whether key omega-3 (n-3) and omega-6 (n-6) fatty acids may be associated with depression, and to explore the role of FADS genotype in PUFA variation. Methods: Four erythrocyte long chain (LC) fatty acids (linoleic acid [LA], α-linolenic acid [ALA], arachidonic acid [AA] and Eicosapentaenoic acid [EPA]), as well as six SNPs (rs174537, rs174547, rs174570, rs174575, rs498793 and rs3834458) within the FADS gene cluster were measured in a sample of 207 participants (154 with MDD versus 53 non-depressed controls). Results: The precursor LC-PUFAs LA and ALA appeared to be negatively associated with depression ( P  < 0.001 and P <  0.01, respectively), while AA:LA (surrogate measure of desaturase activity) was positively associated with depression ( P <  0.01). No significant differences were noted in erythrocyte EPA, AA or AA:EPA between groups. Minor alleles of each SNP (excluding rs498793) were associated with variation in desaturase activity and LA. Both rs174537 and rs174547 were associated with ALA. No genotype was associated with EPA or AA. Minor alleles of rs174537 and rs174547 were significantly associated with lower odds of MDD (although significance was lost after correction for multiple comparisons). Conclusion: Precursor LC-PUFAs, LA and ALA, appear to be associated with MDD and potentially modulated by genetic variation in the FADS gene cluster. These results provide support for the consideration of PUFA composition, diet and FADS genetic variation in the pathophysiology of MDD.